Availability of Resources for After-Hours Surgical Management of Eye Injuries - Chen, Tina H.; Colby, Kathryn A.; Rodriguez, Sarah Hilkert; Slidell, Mark B.; Kandel, Jessica J.; Shah, Hassan A. (Journal of Academic Ophthalmology, 2018)
Background Approximately 2.4 million eye injuries per year occur in the United States. Because of the complexity of these injuries, many of these cases present to academic institutions. Ophthalmology residency programs have a wide range of resources available for eye injuries requiring after-hours surgical intervention.Purpose The purpose of this study was to determine availability of resources for after-hours eye surgery and their effect on clinician satisfaction.Methods Association of University Professors of Ophthalmology (AUPO) program directors were surveyed to assess the availability of eye-trained operating room (OR) nurses, functional operating microscopes, and suitable surgical supplies. The primary outcome measure was the availability of resources for after-hours eye surgery. Secondary outcome measures included the impact of resources on clinician satisfaction.Results Fifty-seven program directors completed the survey. Most programs operated at level 1 trauma centers (95%), had access to a functional microscope (95%), and had frequent adequate surgical supplies (88%). On the other hand, only 28 (49%) programs reported consistent access to OR nurses with ophthalmologic training. Clinician satisfaction scores were three times higher for programs with frequent access to trained surgical OR staff than for programs without (p < 0.001).Conclusion Approximately half of programs report consistent access to ophthalmologic-trained OR staff after hours. In contrast, most programs report access to a functional microscope and surgical supplies. The results of this survey suggest that directing resources toward improving access to after-hours staffing with specialty OR staff may improve clinician satisfaction.
Keywords: after-hours eye surgeries; ocular trauma; operating room resources; clinician satisfaction; survey; listserv